A MANAGERIAL APPROACH OF CUSTOMER SATISFACTION DRIVERS IN THE CLOTHING INDUSTRY - Sunhilde CUC (Management & Marketing)
More than ever customer satisfaction has become a key factor for all industry and business enterprises. The article explains about the customers satisfaction esspecialy in the textile industry. First part presents the concept of customer satisfaction and its place in current management models and tools. The following are the main theories on customer satisfaction with application on textile sector. The key factors affecting customer satisfaction is considered as: perceived service quality, perceived product quality and brand image. We intend also to explain why the ecological products have a more important role in the costumes perception.